A comparison of comparisons: Evidence from an international comparative study of 'smart cities' - WARD, Kevin (Institutional Knowledge at Singapore Management University, 2025)
Every year the list lengthens of cities with some sort of ‘smart city’ public policy. In some, it emerges as the latest in a long line of urban digital and information communication policies. In others, the introduction of the notion of the ‘smart city’ marks a departure from past approaches to public policy. Additionally, the more studies emerge of actual smart city policies, then the less definitional agreement there seems to be. Nevertheless, that we have witnessed in the last two decades the ‘repeated instance’ of smart cities emerging in cities around the world seems incontrovertible. Like so much urban public policy in the current era, how a city arrives at, and makes up, its own version of the ‘smart policy’ often involves comparison and referencing. This is the work of actually existing urban comparisons, those comparisons performed by urban policy makers. This paper draws upon an international comparative research project involving the cases of Barcelona, Calgary, Singapore, Seoul, Taipei, and Toronto. It argues that it is hard to over-estimate the place of cities in the world and the world in cities when understood through the lens of smart city public policymaking. In the cases of the six cities, comparison and referencing of other smart city policies constituted a mode of governance and shaped each city’s policies, as informational infrastructures promoted inter-urban comparisons. This demands we attend to both the routes (their journeys)-and the the roots (their origins) dialectically present in any particular city’s smart city public policy.